Fraud Concerns and Support for Economic Relief Programs - Ingar K. Haaland; Andreas Olden (Center for Economic Studies and ifo Institute (CESifo), 2022)
Using a probability-based sample of the Norwegian population, we test whether an informational treatment about fewer audits by the Norwegian Tax Administration during the peak of the COVID-19 crisis affects support for an economic relief program designed to save jobs and prevent bankruptcies. The information treatment significantly reduces support for the economic relief program. The underlying mechanisms are lower trust in the tax administration's handling of the program and more pessimism about its ability to detect fraud.
Keywords: D83; H25; H26; 330; policy preferences; economic relief programs; information; audit activities